Naringenin protects against scopolamine-induced dementia in rats - Hala F. Zaki; May A. Abd-; Amina S. Attia (Faculty of Pharmacy, Cairo University, 2014)
Background: Alzheimer's disease (AD), the most common cause of progressive dementia in the elderly population, is a chronic neurodegenerative disorder that leads to disturbances of cognitive functions. Although the primary cause of AD remains unclear, brain acetylcholine deficiency and oxidative stress are principal pathogenic factors. Aim of the study: The present study was constructed to investigate the anti-amnestic effect of naringenin on scopolamine-induced behavioral and neurochemical changes in rats. Methods: Naringenin (50 and 100 mg/kg) and donepezil (2.5 mg/kg) were orally administered for 7 successive days. Dementia was induced at the end of the treatment period by a single injection of scopolamine (20 mg/kg; i.p.). Conditioned avoidance and Y-maze tests were conducted 30 min thereafter then rats were sacrificed and brain homogenates were used for the estimation of noradrenaline, dopamine, serotonin and γ-amino butyric acid contents along with acetylcholinesterase activity. In addition, certain inflammatory and oxidative stress markers as well as histopathologic studies were performed. Results: Scopolamine resulted in memory impairment that was coupled by alterations in the estimated neurotransmitters and acetylcholinesterase activity as well as increased brain oxidative stress. Pretreatment of rats with naringenin in both doses mitigated scopolamine-induced behavioral, neurochemical and histological changes in a manner comparable to donepezil. Conclusions: The observed anti-amnestic effect of naringenin makes it a promising candidate for clinical trials in patients with cognitive impairment.